Publications on health systems in Peru between 2000-2020: bibliometric characteristics - Meneses, Giovanni (2023)
Objective: To characterize the publications on Health Systems produced in Peru between 2000-2020. Study: A bibliometric study of the scientific publications on health systems in Peru was carried out in journals indexed in the PubMed and SciELO databases. Narrative reviews, original articles with cross-sectional, and retrospective or prospective designs, were included. Collaboration networks of authors and institutions were described. Findings: 136 bibliographic units were identified. The institutions with the highest production were Universidad Peruana Cayetano Heredia (24.52%), the Ministry of Health (14.19%) and the Universidad Peruana de Ciencias Aplicadas (7.74%). The most studied component was the provision of services (50%), with descriptive designs. 65.44% were published between 2015-2020 and 35.29% in the Revista Peruana de Medicina Experimental y Salud Pública. 51.47% of the articles were written in English. The predominant approach was qualitative (52.94%). Conclusions: The publications on health systems in the period studied focused on the provision of services; they were predominantly qualitative articles.